Pengaruh Kepemimpinan Transformasional dan Transaksional terhadap Kinerja Karyawan dengan Komitmen Organisasi sebagai "Intervening Variable" - Siti Noor Hidayati (Jurnal Maksipreneur, 2014)
Organizational commitment plays a role in determning the employee’s performance. Such a commitment is affected by transformational and transactional style of a leadership. Effects of transformational and transactional style of a leadership toward the employee’s performance are to be determined, with organizational commitment as the intervening variable. Research on 70 employees of CV. CGY showed that the transformational and transactional leadership style, partially and wholly, affect the organizational commitment positively and significantly. The effect of the transformational leadership style is more dominant than the transactional style.